Investigating the effect of solid powder particle type on the turbulent multiphase flow in pipelines - Kor, Yue Kim (2010)
Drag has long been identified as the main reason for the loss of energy in fluid transmission like pipelines and other similar transportation channels. The main contributor to this drag is the turbulence of the flow as well as friction against the pipe walls, which will results in more pumping power consumption. In this study, metal solid particle (i.e. iron and nickel)’s role as a drag reducing agent was investigated. The experimental procedure was divided into two parts; to study the effect of metal particle addition on the turbulent multiphase flow, where the metal type, concentration and particle size served as testing variables. The other part was to investigate the influence of magnetic field on the turbulent flow behavior in pipelines. A custom-made portable magnetic device was used to apply magnetic force to the flow in the pipe. It was concluded that iron solid particles are better and suitable drag reducing agent compared to nickel particles. The experimental results also showed that the drag reduction is more superior towards smaller particle sizes and higher particle concentration. The presence of turbulence can be reduced under the influence of magnetic field; stronger magnetic field increases the effectiveness of drag reduction. But, the effect of magnetic field decreases as Reynolds Number (Re) increases. The maximum value recorded for nickel is 54% taken at Re = 52155 for concentration 500ppm. While for iron particle of size 45µm, the highest drag reduction value reached 46% and highest value; 38% for size 120µm both at concentration 500ppm.